Effects of Copaiba Oil Topical Administration on Oral Wound Healing. (21st June 2017) - Wagner, Vivian Petersen; Webber, Liana Preto; Ortiz, Lisley; Rados, Pantelis Varvaki; Meurer, Luise; Lameira, Osmar Alves; Lima, Rafael Rodrigues; Martins, Manoela Domingues
Abstract : The effects of topical copaiba oil extract and topical corticosteroid were assessed on oral wound healing in an in vivo model using 96 male Wistar rats. Traumatic ulcers were caused in the dorsum of the tongue using a 3‐mm punch tool. The animals were divided into: Control; Corticosteroid; Placebo and Copaiba oil Group. The animals received two daily applications of the products. The control group received only daily handling. Six rats in each group were euthanized at days 3, 5, 10 and 14. The animals were monitored daily to determine wound status. The weigh was assessed at day 0 and euthanasia day. The percentage of repair was calculated, and histopathological aspects were analyzed. The Kruskal–Wallis test was used to compare the results between groups and times of evaluation. Closing time was assessed through the log‐rank test. The corticosteroid group lost more weight at days 10 and 14 than the control group ( p  < 0.05). Moreover, the healing time of corticosteroid group was longer than the control group ( p  = 0.007). No differences were observed between the copaiba oil group and the control group. We concluded that topical copaiba oil, in spite of being safe, did not accelerate the process of oral wound healing. Copyright © 2017 John Wiley & Sons, Ltd.